2021
DOI: 10.1007/s40618-021-01712-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation models for primary thyroid lymphoma, based on the SEER database and an external validation cohort

Abstract: Purpose Primary thyroid lymphoma (PTL) is a rare malignancy, and the literature is limited to small case series and case reports. This study aimed to assess the epidemiologic characteristics, survival, and prognostic factors of patients with PTL. Methods We analyzed 2215 PTL patients from the Surveillance, Epidemiology, and End Results database medical records, between 1983 and 2015, as the training cohort. We enrolled 105 patients from the Cancer Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…With regards to stage at diagnosis, at the end of last century, it was reported that almost 80% of patients have limited disease [32,33]. A more recent study in 2015 reported that 92.1% of patients had Ann Arbor stage I–II disease [34] similar to a more recent one in 2022 showing that 87.6% of new PTL cases were Ann Arbor stages I–II [2 ▪▪ ]. The very small percentage of more advanced stages could be explained by the lack of histological markers that allow differentiation between PTL and those lymphomas that are metastatic to the thyroid gland with the latter group more likely to be diagnosed as metastatic disease to the thyroid gland as opposed to PTL.…”
Section: Stagingmentioning
confidence: 69%
See 3 more Smart Citations
“…With regards to stage at diagnosis, at the end of last century, it was reported that almost 80% of patients have limited disease [32,33]. A more recent study in 2015 reported that 92.1% of patients had Ann Arbor stage I–II disease [34] similar to a more recent one in 2022 showing that 87.6% of new PTL cases were Ann Arbor stages I–II [2 ▪▪ ]. The very small percentage of more advanced stages could be explained by the lack of histological markers that allow differentiation between PTL and those lymphomas that are metastatic to the thyroid gland with the latter group more likely to be diagnosed as metastatic disease to the thyroid gland as opposed to PTL.…”
Section: Stagingmentioning
confidence: 69%
“…PTL is more common in female individuals and has a female-to-male ratio of 4–2.5 to 1 [2 ▪▪ ,3] with a mean age at diagnosis around 65 years of age [3]. PTL frequently occurs in patients with preexisting Hashimoto thyroiditis being this the only associated risk factor carrying almost 60 times higher risk in those with Hashimoto thyroiditis compared with those without [4].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Study subject data were downloaded from the official website of the SEER database (https://seer.cancer.gov/, covering 18 registries including samples from 2000-2018) using SEER*Stat (Version 8.3.9.2, https://seer.cancer.gov/data-software/). Samples were included if they (1) were from 2000-2015 (because Ann Arbor staging was not updated after 2016) (2), had an ICD-O-3 (International Classification of Diseases for Oncology, Third Edition) code 9670 to 9699 or 9728 (7,8), (3) had a primary site code of 73.9 for thyroid gland, and (4) the sequence number indicates the only primary or first primary tumors. Samples were excluded if (1) the primary site surgery was unknown, (2) race of the patient was unknown, (3) survival month was 0 or unknown, or (4) Ann Arbor Stage was unknown (Figure 1).…”
Section: Patient Selection and Data Processingmentioning
confidence: 99%